Impact of the SARS-CoV-2 Pandemic on the Prevalence and Incidence of Gastrointestinal Viruses in Children up to Five Years Old: a Retrospective Cohort Study - Alfredo Maldonado-Barrueco; Julio García-Rodríguez; Jorge Yániz-Ramirez; Irene Serrano-Vaquero; Juan Carlos Parra-Alonso; Carlos Vega-Nieto; Guillermo Ruiz-Carrascoso (Microbiology Spectrum, 2022)
ABSTRACT The aim is determining the impact of non-pharmaceutical measures (NPIs) against SARS-CoV-2 in the incidence and prevalence of gastrointestinal viruses (GV) in children. Demographic, analytical, and clinical data of children from which samples were received at the Hospital Universitario La Paz (Madrid, Spain) and that had a gastrointestinal infection with a positive sample through multiplex-PCR for GV were collected. The time periods included were prepandemic (P1): March 14, 2019 to March 14, 2020 and pandemic (P2): March 15, 2020 to March 15, 2021. The global prevalence, relative incidence (RI, per 1,000 admissions) and absolute incidence (AI, per 100,000 population) of GV were compared for both time periods. The prevalence of GV versus SARS-CoV-2 was determined for P2. Seven-hundred and 50 out of 2,547 children analyzed in P1 and 106 out of 1,368 in P2 were positive by PCR for GV (46.3% decrease in P2). Prevalence and RI of GV declined in P2, except for the RI of rotavirus. Adenovirus showed the largest decreased of prevalence and RI (100%), followed by sapovirus. Astrovirus reduction was less pronounced (3.1% versus 0.4%). Norovirus was the most frequent virus in both time periods and its prevalence and RI also decreased in P2 (15.2% versus 4.7% and 3.40 versus 1.74, respectively). Rotavirus had the smallest decrease in prevalence (2.6% versus 2.5%), and its RI increased during P2 from 0.7 to 0.93. After removing the rotavirus vaccine strains from the analysis, the prevalence and RI decreased during P2 (2.1% to 0.7% and 0.5 to 0.3, respectively). The AI decreased during P2 in all GV, and the prevalence of SARS-CoV-2 and GV was inversely proportional over time. Prevalence and incidence of GV have decreased during the pandemic, probably due to the implementation of NPIs against this virus and the reduction of health care attention to infections other than COVID-19. The differences in the decrease of prevalence and incidence for each virus may be explained by differences in the transmission and the resistance in the environment. Prevalence and RI of rotavirus might be biased since the PCR used detects both the infecting and the vaccine strains. IMPORTANCE Our original article contains an analysis of the impact of the measures applied against SARS-CoV-2 on the prevalence and incidence of GV in children. The small number of studies published to date that analyze the impact of these measures individually on each of the GV makes our study of great interest at this time.